Dissemination of Technology for the Use of Biofertilizers and Biopesticides for Women's Farmer Groups : Diseminasi Teknologi Pemanfaatan Agen Hayati Biofertilizer dan Biopestisida Bagi Kelompok Tani Wanita - Sutarman (Procedia of Social Sciences and Humanities, 2022)
The use of chemicals will be increasingly abandoned considering that they can reduce soil fertility, cause environmental pollution, and are often ineffective. The socialization of biological fertilizers and pesticides technology at the Women Farmers Group (KTW) "Lestari" Pungging Village (Mojokerto Regency) aims to provide a basic understanding of biological agents and create technical mastery of their use and disseminate information so as to encourage all farmers to apply alternative fertilizers and pesticides chemistry. The problem faced by KTW members is that they do not understand at all the knowledge of the characteristics and roles and technology of using biological agents. The solutions are: (i) introducing and providing an understanding of biological agents as an alternative to chemical fertilizers and pesticides, and (ii) increasing the intensity of their knowledge and understanding to be able to socialize the use of biological agents. Implementation methods include: observing the characteristics of KTW, counseling and training related to biological agents and their formulations, planning and implementing Pre-Production of Biological Fertilizers and Pesticides, and evaluation. All activities will be carried out from August 2021 to February 2022. The result of this biotechnology dissemination activity is a change in the basic level of understanding about the characteristics of effective fungal biological agents, from 0% to 65%. Pre-production cadres and implementers prepare pre-production plans, design packaging, determine cost of goods sold, promotion and sales plans. This achievement shows the capacity of KTW cadres in promoting the use of biological agents by farmers.